462 Factors Associated with Longer Post-Operative Hospital Stay Following First Time Coronary-Artery-Bypass-Graft (CABG). (12th October 2021) - Ishak, L; Morcos, K; Curry, P
Abstract: : Prolonged post-operative hospital stay is associated with worse patient healthcare outcomes. Aim: To identify parameters which correlate with longer post-operative hospital stay (POHS) following first time Coronary-Artery-Bypass-Graft (CABG) Method: Data was collected retrospectively on 50 patients who underwent a first time CABG between 12/02/2020 – 21/09/2020 at the Golden Jubilee National Hospital (GJNH). Data included patient demographics, body-mass-index (BMI), presence of co-morbidities, peri-operative blood results, pre-operative renal dysfunction, left ventricular systolic dysfunction (LVSD), severity of left main stem disease, New York Heart Association (NYHA) Functional Classification score, number of grafts, cross-clamp time and bypass time. Results: The mean POHS was 7.5 days. Patients with a POHS>7.5 days had a total mean POHS twice as long (12.07 vs 5.7 days, p < 0.001). They spent more time in intensive care unit (2.6 vs 0.97 days, P = 0.05), high dependency unit (2.5 vs 1.2 days, p = 0.005) and ward (7 vs 3.5 days, p = 0.001) compared to the shorter POHS group. They had a higher mean age (69 vs 65, p = 0.036), lower mean CrCl (80.32 vs 95.14, p = 0.141), higher mean renal dysfunction severity grades (0.8 vs 0.28, p = 0.014), higher mean LVSD severity grades (0.33 vs 0.17, p = 0.35) and higher mean NYHA scores (2.2 vs 1.88, p = 0.17). More of the patients had renal dysfunction (p = 0.01), were on ≥ 2 anticoagulants (p = 0.028), had sub-optimal pre-operative bloods (p = 0.075) and required blood transfusion post-operatively (p = 0.02). One patient in the longer POHS group died. Conclusions: Longer POHS was associated with older age, worse renal function, presence of co-morbidities, sub-optimal peri-operative blood levels and requirement for post-operative blood transfusions.